MAJOR PARAMETERS AFFECT THE NON-LINER RESPONSE OF STRUCTURE UNDER NEAR-FAULT EARTHQUAKES - Mohsin, Ali Abdulwahid; Risan, Hussam K. (Salehan Institute of Higher Education, 2019)
Near-fault ground motion can be identified by the presence of a predominant long duration pulse in the velocity traces mainly due to directivity effect. This pulse exposes the structure to high input energy at the beginning of the earthquake which leads to a higher response in comparison with the ordinary ground motions. This paper investigates 79 earthquake records with different properties to achieve three goals: the first aim is to compare between the linear and nonlinear response of SDOF systems under near-fault and far-fault earthquakes. While the second objective is to examine the parameters that control the characteristics of near-fault earthquakes. Two factors have been studied which is PGV/PGA ratio and pulse period. Finally, the seismic code provisions related to the near-fault earthquakes were evaluated in term of the elastic acceleration response spectrum, the evaluation is adopted for American Society of Civil Engineers code ASCE 7 and Uniform Building Code UBC. The results lead to the following conclusions: with respect to a specific PGA, the near-fault earthquake imposed higher response in comparison with far-field earthquakes. The near-fault earthquakes become severe as the PGV/PGA and pulse period increase. The interested seismic codes can cover the actual behavior based on the average response of a certain amount of data, while it may become non-conservative relative to an individual record.